2020
DOI: 10.1038/s41598-020-71230-4
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose ameliorates peritoneal fibrosis by promoting Snail degradation and inhibiting mesothelial-to-mesenchymal transition in mesothelial cells

Abstract: Peritoneal fibrosis (PF) is a severe complication of peritoneal dialysis, but there are few effective therapies for it. Recent studies have revealed a new biological function of trehalose as an autophagy inducer. Thus far, there are few reports regarding the therapeutic effects of trehalose on fibrotic diseases. Therefore, we examined whether trehalose has anti-fibrotic effects on PF. PF was induced by intraperitoneal injection of chlorhexidine gluconate (CG). CG challenges induced the increase of peritoneal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We detected 30 potential chemicals in BBJ by the method of LC/MS, which is consistent with previous studies ( Chen et al, 2010 ; Yang and Jiang, 2010 ). Importantly, trehalose, quercetin, rutin, ferulic acid, abscisic acid, and trolox were reported to relieve fibrosis by inhibiting TGF-β ( Galicia-Moreno et al, 2008 ; Bruzzone et al, 2012 ; Pan et al, 2014 ; Mu et al, 2018 ; Liu et al, 2019 ; Miyake et al, 2020 ). These phytochemicals were all found in BBJ and may have contributed to the anti-lung fibrosis function of BBJ.…”
Section: Discussionmentioning
confidence: 99%
“…We detected 30 potential chemicals in BBJ by the method of LC/MS, which is consistent with previous studies ( Chen et al, 2010 ; Yang and Jiang, 2010 ). Importantly, trehalose, quercetin, rutin, ferulic acid, abscisic acid, and trolox were reported to relieve fibrosis by inhibiting TGF-β ( Galicia-Moreno et al, 2008 ; Bruzzone et al, 2012 ; Pan et al, 2014 ; Mu et al, 2018 ; Liu et al, 2019 ; Miyake et al, 2020 ). These phytochemicals were all found in BBJ and may have contributed to the anti-lung fibrosis function of BBJ.…”
Section: Discussionmentioning
confidence: 99%
“…In response to many stimuli such as high glucose and inflammatory factors, PMCs can undergo EMT that is characterized by loss of cell adhesion, decreased expression of E-cadherin, and increased expression of α-SMA and β-vimentin [ 15 , 26 ]. Twist and Snail, the two major transcription factors, play a critical role in driving EMT process [ 9 , 27 ]. In this study, we found that delayed administration of nintedanib inhibited CG-stimulated upregulation of Snail or Twist, along with downregulation of β-vimentin, α-SMA, and retained E-cadherin expression.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that α-SMA plays an important role in fibrosis. 12 In addition, collagen I and survivin are known to be positively associated with the progression of fibrosis. 33 , 34 Consistent with these previous findings, in the present study, DHA inhibited the formation of HS via the inhibition of α-SMA, survivin and collagen I. Additionally, it has been reported that the activation of α-SMA promotes the epithelial-mesenchymal transition (EMT) process.…”
Section: Discussionmentioning
confidence: 99%
“…10 The aberrant occurrence of autophagy can lead to the dysfunction of cellular organelles. 11,12 On the other hand, autophagy protects organisms from inflammatory injuries via the modulation of the apoptotic cascade. 13 Recent studies have revealed that autophagy plays a crucial role in the formation of HS; [13][14][15] however, the association between DHA and cell autophagy in HS remains unclear.…”
Section: Introductionmentioning
confidence: 99%